2008
DOI: 10.1021/jp8027879
|View full text |Cite
|
Sign up to set email alerts
|

Does an Ethene/Benzenium Ion Complex Exist? A Discrepancy between B3LYP and MP2 Predictions

Abstract: To investigate the possible existence of a complex between the benzenium ion and ethene, computations employing B3LYP and MP2 were carried out. The two methodologies gave conflicting answers; B3LYP confirmed the existence, but according to MP2, the structure found by B3LYP transforms into an ethylbenzenium ion. Computations utilizing the CCSD and QCISD methods showed the B3LYP result to be correct; 21 kJ/mol is needed to separate the two moieties.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
41
0

Year Published

2009
2009
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(41 citation statements)
references
References 9 publications
0
41
0
Order By: Relevance
“…Secondly, in the transition state the ethyl side-chain and aromatic ring are nearly parallel, indicating the formation of an alkyl-benzene like complex (see Figure 3c), which is stabilized by non-covalent interactions 1 . [22,26,28,29] We also modeled a transition state that does not exhibit this particular complex formation and 1 With the M06-2X functional a similar geometry and free energy barrier were found for reaction E1 obtained a free energy barrier of 245 kJ/mol ( Figure S3 and Table S2 of the SI). Finally, the assisting water molecule eases the deprotonation of the ethyl group by facilitating the access to the active site (see Figure 3d).…”
Section: Resultsmentioning
confidence: 69%
“…Secondly, in the transition state the ethyl side-chain and aromatic ring are nearly parallel, indicating the formation of an alkyl-benzene like complex (see Figure 3c), which is stabilized by non-covalent interactions 1 . [22,26,28,29] We also modeled a transition state that does not exhibit this particular complex formation and 1 With the M06-2X functional a similar geometry and free energy barrier were found for reaction E1 obtained a free energy barrier of 245 kJ/mol ( Figure S3 and Table S2 of the SI). Finally, the assisting water molecule eases the deprotonation of the ethyl group by facilitating the access to the active site (see Figure 3d).…”
Section: Resultsmentioning
confidence: 69%
“…The total energies were calculated using density functional theory (DFT) and generalized gradient approximation (GGA) for exchange correlation potential (B3LYP) [18]. While a number of GGA functionals are available, our choice of B3LYP functional was motivated by the pioneering work of Kolboe and Svelle [19], where they showed that the B3LYP functional confirmed the existence of a complex between the benzenium ion and ethene, in agreement with higher level calculations such as CCSD and QCISD. The atomic orbitals are represented by a Gaussian basis and we used the SDD basis set in our calculations.…”
Section: Methodsmentioning
confidence: 87%
“…As such, density functional theory (DFT) [46] was chosen as our standard calculation method because it has been employed successfully in studies of intermolecular systems [47][48][49]. Using a robust capability test, Xu et al [50] revealed that B3LYP is a valuable functional in view of the small errors associated with the prediction of the relative binding energies of intermolecular systems [51][52][53].…”
Section: Methodsmentioning
confidence: 99%